Analyzing the Lyrics of 'How Do I Live': A Study on Textual and Contextual Perspectives - Patty, Jusak; Que, Stella Rose (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2023)
This discourse analysis focuses on the emotional narrative of Diane Warren's song